Effect of a shore-based sampling programme on Notothenia coriiceps populations - Casaux, Ricardo Jorge; Barrera Oro, Esteban (Antarctic Science)
The effect of an intensive sampling programme on an inshore population of Notothenia coriiceps was studied at Potter Cove, South Shetland islands, by comparing catch data taken in successive summers of 1992/93 to 1994/95 at one specific zone (site 1) with those taken in the 1994/95 summer at two close but not previously sampled zones (sites 2 and 3). The fish were caught with trammel nets under similar sampling conditions (depth, net measurements, bottom type). In site 1, a decline in length (TL) of the fish was observed throughout the whole period. The fish from sites 2 (mean = 32.4 cm) and 3 (mean = 31.8 cm) exhibited no significant differences in mean length. They were larger (P = 0.07) than those from site 1 caught in the summers of 1994/95 (mean = 28.8 cm) and 1993/94 (mean = 30.2 cm), but were similar in size to those sampled in the summer of 1992/93 (mean = 31.7 cm), just when the sampling programme started in site 1. Although alternative hypotheses to explain the results are discussed (e.g. random error, strong recruitment), it is suggested that the size variations of the fish sampled at site 1 are due to intensive sampling effort carried out throughout this study at that specific zone in Potter Cove. Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina